2018
DOI: 10.1590/1806-9061-2017-0526
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Tarragon (Artemisia Dracunculus) Powders in Different Levels on Carcass Characteristics and Some Internal Organ’s Weight of Broiler Chickens

Abstract: This study was conducted to investigate the effects of different levels of Tarragon powder on head, chicken feet, some internal organs and carcass characteristics of broiler chickens. One day -old two hundred forty Ross 308 male broilers were randomly allocated into four treatments and six replicates per treatment. At each replicate ten birds were used. All birds at 42 days had ad libitum access to water and feed and were exposed to a 23L:1D lighting program. The diets were set on the basis of corn, soybean an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…In this study, dietary supplementation with AD induced significant improvements in WG and SGR in rainbow trout specimens. Improved growth performance in fish may be due to the effect of tarragon extract on pancreatic function (Aggarwal et al, 2015; Yildirim & Tunç, 2018). Also, the phenolic and aromatic compounds present in AD extract may have a significant effect on increasing fish appetite.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, dietary supplementation with AD induced significant improvements in WG and SGR in rainbow trout specimens. Improved growth performance in fish may be due to the effect of tarragon extract on pancreatic function (Aggarwal et al, 2015; Yildirim & Tunç, 2018). Also, the phenolic and aromatic compounds present in AD extract may have a significant effect on increasing fish appetite.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the phenolic and aromatic compounds present in AD extract may have a significant effect on increasing fish appetite. In this sense, the use of tarragon extract to increase appetite is traditionally common (Yildirim & Tunç, 2018). Yildrim and Tunç (2018) found that administering tarragon to quails could increase appetite by increasing gastrointestinal secretions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, due to its level of terpene, tarragon has been used to treat gastrointestinal complaints, such as diarrhoea (Kumlay et al 2015, Jalilzadeh-Amin andMaham 2015). There are a few studies about the use of tarragon as a feed additive in poultry nutrition (Yildirim and Tunç 2018, Gharetappe et al 2015, Sen et al 2012, Incharoen et al 2009, but this study provides more extensive research in terms of nutrients and health. The purpose of this study is to investigate the effect of tarragon powder on performance and histological changes of organs in broiler chickens.…”
Section: Introductionmentioning
confidence: 91%